A Study on the Impact of Social Media Strategies on Employer Branding at TCS, Nagpur - Mendhe, Pallavi Ghansham; Ukunde, Smita (Journal of Neonatal Surgery, 2025)
Employer branding has emerged as a critical factor in attracting and retaining top talent, particularly in the IT sector. Social media strategies play a pivotal role in shaping how potential employees perceive an organization. This study explores the impact of social media strategies on employer branding at Tata Consultancy Services (TCS), Nagpur. It investigates how TCS leverages platforms such as LinkedIn, Instagram, Facebook, and Twitter to build a robust employer brand and enhance its appeal to job seekers. The research highlights the relationship between consistent online presence, audience engagement, and perception management in fostering a positive employer image. Data for this study were collected through a combination of surveys and secondary sources to understand the effectiveness of social media initiatives on employer branding. Key findings indicate that social media strategies significantly enhance brand visibility, employee trust, and recruitment efficiency. Moreover, the study sheds light on how content quality, relevance, and engagement metrics contribute to creating a compelling employer narrative. The research underscores the importance of aligning social media practices with organizational values to maintain authenticity and credibility. Implications of these findings are crucial for HR professionals seeking innovative ways to strengthen employer branding through digital mediums. Recommendations include adopting a dynamic content strategy, regular monitoring of engagement metrics, and incorporating employee advocacy programs to amplify brand communication. This paper provides a comprehensive understanding of how strategic use of social media platforms can redefine employer branding, ultimately improving organizational competitiveness in the talent acquisition landscape.